PWE-162 Lap band unclipping and reclipping, should the patient keep the band?. (22nd June 2015) - Houghton, J; Keogh, K; Merker, L; Wilson-Evans, D; Hewes, J
Abstract : Introduction: After initial enthusiasm it has become apparent that laparoscopic gastric bands are prone to complications including formation of fibrous capsules leading to dysphagia and vomiting. Gastric bands are often unclipped and then reclipped after division of the fibrous capsule. We analyse the outcomes of these patients to assess whether keeping the band is beneficial or if removing the band at first revision is advisable. Method: Patients having revisional surgery to their gastric band were identified through an online patient management system in a high volume bariatric centre. Prospectively recorded electronic patient records were examined to identify patient demographics and key events in the patient pathway. The primary outcome measure was removal of the band. Results: The period of assessment was from March 2009 to March 2014. Over that period 772 laparoscopic bands were inserted in this trust and 101 (13%) were removed. During the assessment period 48 patients had gastric bands unclipped or changed with division of fibrous capsule (including patients whose bands were inserted in other centres). The median age of these patients was 43 at insertion of band. The median duration from gastric band insertion to revision was 26 months. The median duration to reclipping was 6 months. 15 (31%) patients went on to have further surgery to have their band removed. Conclusion: Gastric bands are a useful tool for treating obesity. While the majority of patients tolerate their band well a significant proportion are associated with fibrous band formation. If patients undergo surgery to unclip the band and divide the capsule this is associated with significant weight gain and a large proportion of patients (31%) will ultimately have their band removed due to intolerance. Patients should be counselled as such before first revision to enable informed choice. Disclosure of interest: None Declared.